A clinicopathological study of histomorphological differentiation and staging of lymph node metastasis in periampullary carcinoma - Chakraborty, Ramit; Chandanwale, Shirish; Gore, Charusheela; Londhe, Mangesh S. (International Journal of Research in Medical Sciences, 2024)
Background: The periampullary region is an anatomically and histologically complex area that is prone towards malignant transformation. Malignancies in this region have increased in incidence in the last few decades. Classifying these malignancies has become crucial for prognosis and treatment. With the pancreato-biliary type being more aggressive as compared to the intestinal type. Lymph node metastasis and lymph node ratio also aid in prognostication. Methods: This prospective descriptive study was conducted over one year from August 2022 on 30 patients diagnosed with periampullary tumors who underwent pancreatoduodenectomy and biopsy. Histopathological classification and prognostic factors were analyzed based on Kimura et al classification. Results: The study included 18 males and 12 females with a mean age of 53.47 years. The origin of the tumor was the head of the pancreas in 66.66% (n=20) of the patients. Adenocarcinoma was the most common histological type. The pancreato-biliary type of adenocarcinoma was more aggressive than the intestinal type when primary tumor size and staging were compared. Conclusions: Periampullary carcinomas are difficult to classify. Kimura et al classification is an important classification system that helps in the treatment and prognostication of the patient. The pancreato-biliary type of adenocarcinoma is more aggressive as compared to the intestinal type. Lymph node metastasis and lymph node ratio are also important prognostic factors.